2007
DOI: 10.1111/j.1751-1097.2007.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Components of Photodynamic Therapy Can Phosphorylate Akt

Abstract: A growing number of clinically relevant molecular and cellular responses are observed following photodynamic therapy (PDT). PDT-mediated oxidative stress and PDT-induced tissue hypoxia can elicit the transcriptional and/or translational expression of genes associated with cellular stress, inflammation, angiogenesis, immuno-modulation, apoptosis and signal transduction. One of the signaling molecules activated by oxidative stress is Akt/protein kinase B. Phosphorylation of Akt/protein kinase B activates this si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
(32 reference statements)
2
16
1
1
Order By: Relevance
“…Likewise, inhibition of Akt did not influence PDT-induced elimination of neuronal activity and apoptosis of glial cells indicating that Akt was not involved in the protection of glial cells from PDT-induced apoptosis and in the regulation of neuron firing. These results were not in agreement with the data on the protective role of the PI3K/Akt pathway in photosensitized mammalian cells, in which PDT not only induced apoptosis but also initiated PI3K/Akt-related pro-survival pathways (Xue et al 1999;Zhuang and Kochevar 2003;Schieke et al 2004;Volanti et al 2005;Bozkulak et al 2007;Kocanova et al 2007;Zheng et al 2008;Espada et al 2009;Ferrario and Gomer 2010). The nonparticipation of PI3K and Akt in the regulation of glial apoptosis was, possibly, a specific feature of the crayfish nervous system.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Likewise, inhibition of Akt did not influence PDT-induced elimination of neuronal activity and apoptosis of glial cells indicating that Akt was not involved in the protection of glial cells from PDT-induced apoptosis and in the regulation of neuron firing. These results were not in agreement with the data on the protective role of the PI3K/Akt pathway in photosensitized mammalian cells, in which PDT not only induced apoptosis but also initiated PI3K/Akt-related pro-survival pathways (Xue et al 1999;Zhuang and Kochevar 2003;Schieke et al 2004;Volanti et al 2005;Bozkulak et al 2007;Kocanova et al 2007;Zheng et al 2008;Espada et al 2009;Ferrario and Gomer 2010). The nonparticipation of PI3K and Akt in the regulation of glial apoptosis was, possibly, a specific feature of the crayfish nervous system.…”
Section: Discussioncontrasting
confidence: 74%
“…The signaling pathway involving phosphatidylinositol 3-kinase (PI3K), protein kinase B/Akt (Akt), and glycogen synthase kinase-3β (GSK-3β) plays usually the protective, anti-apoptotic role (Krasilnikov 2000;Duronio 2008). Along with induction of necrosis and apoptosis, PDT is known to activate the protective PI3K/Akt pathway in diverse cell lines (Xue et al 1999;Zhuang and Kochevar 2003;Schieke et al 2004;Bozkulak et al 2007;Espada et al 2009). However, the role of downstream enzymes such as GSK-3β in photodynamic cell damage, particularly in nerve tissue injury, has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier investigation proved that nasopharyngeal cells maintained in hypoxic condition induce the expression of the PDGF-b gene whereas upregulation of HIF-1a was observed both in hypoxic and normoxic environment [30]. Interestingly, Buzkulok et al [64] demonstrated that individual components of the PDT process, photosensitizer alone and light alone as well as the complete PDT procedure, could activate the Akt signaling pathway in murine and human breast cancer cells and tumors. Wei et al [65] demonstrated in epithelial tumor cells that while the action of IL-6 cytokines through their membrane receptors is attenuated, regulation by IL-6 via trans-signalling is established, thus enhancing PDT.…”
Section: Matrix Metalloproteinasesmentioning
confidence: 96%
“…In a recent study, the same group also demonstrated that Akt phosphorylation was induced by multiple PDT components in in vitro and in vivo treatments. Additionally, they demonstrated that blockage of Akt phosphorylation using P13-K inhibitors can increase PDT-mediated apoptosis within treated cells [64].…”
Section: Combination Of Pdt and Angiogenesis Inhibitorsmentioning
confidence: 99%
“…The potentialities of modern oncology were essentially extended with the development of photodynamic therapy (PDT), a modern organ-sparing therapeutic method, based on selective laser exposure of tumor tissues and cells pre-sensitized by a tumorotropic stain [4,5]. However, despite the progress in development of this method, relapses sometimes emerge after therapy [6], and hence, combination of PDT with other methods used for cancer treatment seems to be a promising trend. One of these methods, though little studied by the present time, is electrochemical lysis (ECL).…”
mentioning
confidence: 99%